2010
DOI: 10.1126/science.1187058
|View full text |Cite
|
Sign up to set email alerts
|

Target RNA–Directed Trimming and Tailing of Small Silencing RNAs

Abstract: In Drosophila, microRNAs (miRNAs) typically guide Argonaute1 to repress mRNA, whereas small interfering RNAs (siRNAs) guide Argonaute2 to destroy viral and transposon RNA. Unlike siRNAs, miRNAs rarely base pair extensively to the mRNAs they regulate. We find that extensive complementarity between a target RNA and an Argonaute1-bound miRNA triggers miRNA tailing and 3′-to-5′ trimming. In flies, Argonaute2-bound small RNAs—but not those bound to Argonaute1—bear a 2′-O-methyl group at their 3′ ends. This modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
661
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 546 publications
(691 citation statements)
references
References 42 publications
24
661
2
4
Order By: Relevance
“…(2) If they are bound, does AGO1 influence 39 modifications? In Drosophila melanogaster, extensive matching between Argonaute1-bound miRNA and its target destabilize miRNA through 39 truncation and tailing (Ameres et al, 2010). By RNA gel blots, immunoprecipitation (IP) of AGO1 showed that it bound the variants of all sizes for miR158 and miR171a in an Arabidopsis hen1 background, with the binding of these variants unaffected in the heso1-1 hen1-8 double mutant ( Figure 5A).…”
Section: Mutations In Ago1 Suppress the Truncation And Tailing Of Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) If they are bound, does AGO1 influence 39 modifications? In Drosophila melanogaster, extensive matching between Argonaute1-bound miRNA and its target destabilize miRNA through 39 truncation and tailing (Ameres et al, 2010). By RNA gel blots, immunoprecipitation (IP) of AGO1 showed that it bound the variants of all sizes for miR158 and miR171a in an Arabidopsis hen1 background, with the binding of these variants unaffected in the heso1-1 hen1-8 double mutant ( Figure 5A).…”
Section: Mutations In Ago1 Suppress the Truncation And Tailing Of Mirnasmentioning
confidence: 99%
“…Plant microRNAs (miRNAs) pair with their targets near-perfectly and are 39 protected by methylation (Voinnet, 2009); by contrast, animal miRNAs are unmethylated and typically partially complementary to their mRNA targets via the short seed region at the 59 end (Bartel, 2009) and can be truncated and tailed when extensively matched by a target RNA (Ameres et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1C). Small RNA remodeling by trimming has been observed [20]. Additionally, also base modifications can improve siRNA stability [21].…”
Section: Trna Modifications Can Affect Trna Fragmentationmentioning
confidence: 99%
“…87 Furthermore, overexpression of pri-miRNA or pre-miRNA with some flanking sequence may be more biologically relevant than simply using the mature miRNA sequence because the transcript may interact with the endogenous cellular machinery, ensuring correct processing and final functionality. 88 A key challenge in the modulation of miRNA signaling for tissue regeneration is the selection of the right therapeutic candidates.…”
Section: Approaches and Cautionmentioning
confidence: 99%